IMPROVISATION OF INSTRUCTIONAL MATERIALS AND SS II ECONOMICS STUDENTS’ ACADEMIC PERFORMANCE IN KAURA LOCAL GOVERNMENT AREA OF KADUNA STATE - Tormoh , Grace Samuel; Job, Gabriel Chibuzor (Journal of Continuing and Development Education, 2024)
The study investigated the effect of improvised instructional materials on the academic performance of SS II Economics students in Kaura Local Government Area of Kaduna State. The downward trend in academic performance of Economics Students, particularly from external examinations has attracted public attention. Two research questions translated to null hypotheses were formulated for the study. Quasi- experimental research design, specifically, pre-test – post-test design was used. A total of sixty (60) students were sampled out from a population of 3,658 students. Data collected were analyzed through the use of descriptive statistics of mean and standard deviation and inferential statistics of independent t-test. The findings from the study revealed that a positive significant difference in academic performance of SS II Students taught Economics with the use of improvised instructional materials when compared with those taught Economics without the use of improvised instructional material at .05 level of significance. It also revealed no significant difference in the performance of male and female taught Economics using improvised instructional materials. It was concluded among others that since the students taught Economics with the use of improvised instructional materials had a better mean score than those taught without the use of improvised instructional materials, there is need for teachers to be trained to improvise as this will enable them acquire the appropriate techniques and skills necessary for improvisation. Hence, it was recommended that Teachers should be trained and re-trained through workshops, seminars and conferences for the purpose of skill acquisition necessary for the production and use of instructional materials by teachers.